If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(8n + -2) = 3 + 10 + -30n Reorder the terms: -1(-2 + 8n) = 3 + 10 + -30n (-2 * -1 + 8n * -1) = 3 + 10 + -30n (2 + -8n) = 3 + 10 + -30n Combine like terms: 3 + 10 = 13 2 + -8n = 13 + -30n Solving 2 + -8n = 13 + -30n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '30n' to each side of the equation. 2 + -8n + 30n = 13 + -30n + 30n Combine like terms: -8n + 30n = 22n 2 + 22n = 13 + -30n + 30n Combine like terms: -30n + 30n = 0 2 + 22n = 13 + 0 2 + 22n = 13 Add '-2' to each side of the equation. 2 + -2 + 22n = 13 + -2 Combine like terms: 2 + -2 = 0 0 + 22n = 13 + -2 22n = 13 + -2 Combine like terms: 13 + -2 = 11 22n = 11 Divide each side by '22'. n = 0.5 Simplifying n = 0.5
| -3x+8+2x=15 | | 15=-3(5x+5) | | 12x-48=30 | | -4(-6x+8)=16 | | y=(-9)-2x | | -5(4t-3)+9t=2t-8 | | 12x-(9x-5)=17 | | 2(x-2)=5(x+3) | | 35n+25=625 | | 20x^3-17x^2+3x=0 | | .9x-6.2=.1 | | n=1.25n+6.25 | | x+(4+32)=32 | | 6x-4(2x+8)=36 | | 3x-9v=5+7v | | 16x+1=13-2x | | 4-3x+5x=6 | | 5x-3=3x-21 | | 49=-7t+(-7) | | 9m-5m+2=4m+2 | | X^2-6X-12X=0 | | 3y=-21+7x | | 2(x+1)(x+4)-(x-2)(x-2)=0 | | 6x+12-8x=20 | | 3*(x+2)-x= | | 15=3(5x+5) | | 12mn+4m+8mn+6m= | | (n-2)180= | | 2v^2+v+64=0 | | -4-4x+2x=-10 | | 1+4x=-31 | | a+-0.4=-3 |